2020
DOI: 10.1142/s1758825120500374
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Free Vibration Analysis of Axially Functionally Graded Beams Integrated with Piezoelectric Layers: An Piezoelasticity Approach

Abstract: For the first time, a two-dimensional (2D) piezoelasticity-based analytical solution is developed for free vibration analysis of axially functionally graded (AFG) beams integrated with piezoelectric layers and subjected to arbitrary supported boundary conditions. The material properties of the elastic layers are considered to vary linearly along the axial ([Formula: see text]) direction of the beam. Modified Hamiltons principle is applied to derive the weak form of coupled governing equations in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…It should be emphasized that the current results are in good agreement with the 3‐D FE except near to the edge. This disagreement at the very clamped support is well‐reported and discussed in literatures [34–36, 45].…”
Section: Numerical Results and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It should be emphasized that the current results are in good agreement with the 3‐D FE except near to the edge. This disagreement at the very clamped support is well‐reported and discussed in literatures [34–36, 45].…”
Section: Numerical Results and Discussionsupporting
confidence: 76%
“…The Reissner‐type variational principle for cylindrical bending analysis of the panel, without any body force source and unit width along y ‐direction, can be expressed as [36] Vfalse[δufalse(σx,xgoodbreak+τxz,zfalse)+δvfalse(τxy,xgoodbreak+τyz,zfalse)+δwfalse(τzx,xgoodbreak+σz,zfalse)+δσxfalse(εxgoodbreak−u,xfalse)+δσzfalse(εzw,zfalse)+δτyzfalse(γyzgoodbreak−v,zfalse)+δτzxfalse(γzxgoodbreak−u,zgoodbreak−w,xfalse)+δτxyfalse(γxygoodbreak−v,xfalse)false]0.16emdVgoodbreak=0,1emδui,δvi,δwi,δσi,δτij$$\begin{eqnarray} && \int _{V} [\delta u (\sigma _{x,x}+\tau _{xz,z})+\delta v (\tau _{xy,x}+\tau _{yz,z})+\delta w (\tau _{zx,x}+\sigma _{z,z}) +\delta {\sigma _{x}}(\epsilon _{x}-u_{,x})+{\delta \sigma _{z}}({\epsilon _z-w}_{,z})+{\delta \tau _{yz}}(\gamma _{yz}-v_{,z}) \nonumber\\ &&\quad +\,{\delta \tau _{zx}}(\gamma _{zx}-u_{,z}-w_{,x})+{\delta \tau _{xy}}(\gamma _{xy}-v_{,x})]\,dV=0,\quad \forall \delta u_{i}, \delta v_{i}, \delta w_{i}, \delta \sigma _{i}, \delta \tau _{ij} \end{eqnarray}$$where V stands for the volume of panel having unit width along the y ‐direction. Now, the expressions of strain components εx…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nan et al [7] explored the static bending and free vibration analysis of porous functionally graded piezoelectric nanobeams utilizing the electric enthalpy variation and Hamilton's principle, as well as differential equations for regulating the bending and free vibration. Using an analytical method, Singh and Kumari [8] investigated the free vibration analysis of axially functionally graded beams that were integrated with piezoelectric layers and subjected to arbitrarily supported boundary conditions in a free-falling state. Larkin and colleagues [9] used the modified couple stress theory to investigate the impact of small-scale phenomena on the natural frequencies and power density of macro-to nanoscale functionally graded energy harvesters with beam lengths ranging from 62.5 mm to 6.25 m. They found that the natural frequencies and power density of the harvesters were affected by small-scale phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the analytical solution in conjunction with Reddy's beam theory was used. Singh and Kumari [16] presented an analytical solution based on piezoelectricity for two-dimensional free vibration analysis of axially FGM beam integrated with piezoelectric layers.…”
Section: Introductionmentioning
confidence: 99%